PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAEWAI PDA KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI SUMATERA BARAT - Sri Handayani; Harif Amali Rivai (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
Abstract: The study in this study on the analysis of the The Influence of Transformational Leadership, Organizational Culture and Motivation on Employee Performance at Regional Office of National Land Agency of West Sumatera Province.  The issues raised in this research are:  How is the influence Transformational Leadership towards Employee Performance at Regional Office of National Land Agency of West Sumatera Province.  (2) How is the influence Organizational Culture towards Employee Performance at Regional Office of National Land Agency of West Sumatera Province. (3 ) How is the influence Motivation towards Employee Performance at Regional Office of National Land Agency of West Sumatera Province In this research using descriptif analyse. This analysis for give deep arguement and implemented hypotesis that describe in quantitatif analyse, based on questioner list has been filled by employee. Then those data is analysed by statistic with using SPSS 16 application for windows  to testing this research hypotesis with cover Multiple Regression analyse .The result of descriptive analysis shows that there is a positive and significant influence between Transformational Leadership toward Employee Performance, there is a positive and significant influence between Organizational Culture toward Employee Performance,  there is a positive and  significant influence Motivation towards toward Employee PerformanceBased on the statistical test of three research variables, it is concluded that Transformational Leadership is the most influential variable to Employee PerformanceKeyword: Transformational Leadership, Organizational Culture and Motivation , Employee Performance